Protecting Group Dynamic Information in Large Scale Multicast Groups - WU, Yongdong (Institutional Knowledge at Singapore Management University, 2005)
Existing key management schemes can secure group communication efficiently, but are failed on protecting the Group Dynamic Information (GDI) that may undermine group privacy. Recently, Sun et al. proposed a scheme to hide the GDI with batch updating and phantom members inserting so that an adversary is not able to estimate the number of group members. In this paper, we first point out that their scheme is only applicable in departure-only group communication instead of the common conference groups. Secondly, we introduce our method of estimating the group size at a higher confidence level given a prior departure probability. Further, to enhance GDI protection and extend the application fields, we propose to protect GDI with two new mechanisms: chameleon member identifications and virtual departure events. The proposed scheme is effective to protect both centralized groups and contributory groups. The simulation shows that our scheme is better on protecting the GDI.